Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Loyalitas Kerja Terhadap Kinerja Karyawan pada CV Cafitex di Sukoharjo - Saraswati, Dian; Sutarno; Sunarso (UNIVERSITAS SERAMBI MEKKAH, 2025)
Employee performance is one of the determining factors for the success of an agency or organization in achieving its goals. One company that has performance problems is CV Cafitex in Sukoharjo. CV Cafitex is a Goyor woven sarong industrial company located in Sukoharjo. This research aims to analyze the significance of the influence of leadership style on employee performance at CV Cafitex in Sukoharjo, the significance of the influence of the work environment on employee performance at CV Cafitex in Sukoharjo. Analyzing the significance of the influence of work loyalty on employee performance at CV Cafitex in Sukoharjo This research uses CV Cafitex employees in Sukoharjo as objects. The research method used is a quantitative method, using SPSS 25.0, to analyze the data. The data sources used in this research are primary data and secondary data. The population in this study were employees of CV Cafitex in Sukoharjo. The sample used in this research was 47 CV Cafitex employees in Sukoharjo. The sampling technique uses proportional cluster random sampling technique. The data collection techniques used were questionnaires, observation and literature study. Data analysis techniques use descriptive analysis, multiple linear regression test, t test, F test, and coefficient of determination test. The results of multiple linear regression analysis in this study are Y = 4.633+ 0.738 X1 + 0.037 X2 + 0.039 X3 . The t test results show that leadership style has a significant effect on employee performance. This shows that changes in leadership style significantly influence the performance of CV Cafitex employees in Sukoharjo. The work environment does not have a significant effect on the performance of CV Cafitex employees in Sukoharjo so that the higher the work environment obtained by employees, the employee performance will not increase. Work loyalty does not have a significant effect on the performance of CV Cafitex employees in Sukoharjo so that the higher the work loyalty of employees, the employee performance will not increase.